A Novel Mutation of HINT1 Gene in an Adolescent Female with Axonal Neuropathy and Neuromyotonia - Kara, Bülent; Gül, Sedat; Güneş, Ayfer Sakarya; Mülayim, Serap; Yeşil, Gözde (Journal of Pediatric Neurology, 2020)
HINT1 gene mutations cause an axonal neuropathy with some specific findings including presence of neuromyotonia, autosomal recessive inheritance, onset in the first decade, and primary motor involvement. In this case report, we described an 18-year-old female patient who presented to the clinic with gait instability and muscle stiffness. A homozygous novel c.180_181delAT (p.Ser61Profs*8) variant in the HINT1 gene was found by clinical exome analysis. Parents were heterozygous for the same variant. The patient was diagnosed with autosomal recessive axonal neuropathy with neuromyotonia. The presence of neuromyotonia must be evaluated in patients with hereditary axonal neuropathies as this can help the diagnosis prior to genetic testing.
Keywords: HINT1 gene; axonal neuropathy; neuromyotonia